2017
DOI: 10.1016/j.ejpb.2016.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution behavior of co-amorphous amino acid-indomethacin mixtures: The ability of amino acids to stabilize the supersaturated state of indomethacin

Abstract: Dissolution behavior of co-amorphous amino acid-indomethacin mixtures : The ability of amino acids to stabilize the supersaturated state of indomethacin Ojaranta, Rami; Heikkinen, Aki T.; Sievänen, Elina; Laitinen, Riikka Ojaranta, R., Heikkinen, A. T., Sievänen, E., & Laitinen, R. (2017). Dissolution behavior of co-amorphous amino acid-indomethacin mixtures : The ability of amino acids to stabilize the supersaturated state of indomethacin. European Journal of Pharmaceutics and Biopharmaceutics, 112, 85-95. do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 43 publications
2
28
1
1
Order By: Relevance
“…In the coamorphous system, drug-drug or drug-excipient interacts with each other and inhibits crystallization at the amorphous state. 9,10) Several researchers have shown that a co-amorphous system improved stability of the amorphous state compared with that of single compound. 11,12) Hence SCL based on the co-amorphous approach, which stabilizes the thermodynamically unstable state by intermolecular interactions, should also improve the stability of the SCL state.…”
Section: Introductionmentioning
confidence: 99%
“…In the coamorphous system, drug-drug or drug-excipient interacts with each other and inhibits crystallization at the amorphous state. 9,10) Several researchers have shown that a co-amorphous system improved stability of the amorphous state compared with that of single compound. 11,12) Hence SCL based on the co-amorphous approach, which stabilizes the thermodynamically unstable state by intermolecular interactions, should also improve the stability of the SCL state.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the studies where supersaturation has been most efficiently stabilized when strong intermolecular interactions have been detected between the components, i.e. amorphous salt formation (Ojarinta et al, 2017;Paluch et al, 2010) or hydrogen bonding (Wang et al, 2017). It is also possible that adsorption on the "surfaces" of nuclei and, in some cases solubilization, may inhibit drug recrystallization.…”
Section: Future Prospects: Novel Preparation Methods For Co-amorphousmentioning
confidence: 92%
“…From the above discussion it can be concluded that co-amorphous salt formation has been proven effective in stabilizing supersaturation. Amorphous salt formation may thus have the best potential for precipitation inhibition of the co-amorphous formulations, as, for example, arginine showed a significant inhibitory effect for indomethacin precipitation in FaSSIF (Ojarinta et al, 2017). However in future, further in vitro evaluation under biorelevant conditions would be necessary to extrapolate in vitro supersaturation assessment to the in vivo situation.…”
Section: Future Prospects: Novel Preparation Methods For Co-amorphousmentioning
confidence: 99%
See 1 more Smart Citation
“…However, thermodynamic instability due to the recrystallization tendency during processing, storage and in contact with the biological fluids, limits the potential application of amorphous systems [ 5 ]. Therefore, new formulation strategies based on solid molecular dispersions are being exploited and co-amorphous dispersions is one of them with very promising results [ 6 ].…”
Section: Introductionmentioning
confidence: 99%